Compact UWB bandpass filter with sharp roll‐off using APCL structure. Issue 13 (1st June 2018) - Xia, Xinlin; Cheng, Xu; Chen, Fengjun; Deng, Xianjin
Abstract : In this letter, a quintuple‐mode bandpass filter for a UWB system with improved performance is presented. The presented filter is implemented with asymmetric parallel‐coupled lines loaded open stub and short stub connected at the symmetrical plane of the filter to increase its frequency selectivity. Five resonant frequencies within the UWB band and two transmission zeros at the lower and upper passband/stopband edges are observed. A filter prototype is fabricated for verification and the experimental data are corresponding well with the simulated results. The proposed filter achieves a bandwidth that can exactly cover the whole UWB frequency band. Moreover, this filter has a compact size (0.645 λ g × 0.318 λ g ) and low insertion loss.